Synergistic voltaglue adhesive mechanisms with alternating electric fields - Singh, Manisha (2020)
Voltage-activated adhesion is a relatively new discovery that relies on direct currents for initiation of cross-linking. Previous investigations have found that direct currents are linearly correlated to the migration rates of electrocuring, but this is limited by high voltages exceeding 100 V with instances of incomplete curing of voltage-activated adhesives on semiconducting substrates. Practical applications of electrocuring would benefit from lower voltages to mitigate high-voltage risks, especially with regard to potential medical applications. Alternative electrocuring strategies based on alternating current (AC), electrolyte ionic radius, and temperature are evaluated herein. Square-waveform AC electric field is hypothesized to initiate a two-sided curing progression of voltage-activated adhesive (PAMAM-g-diazirine, aka Voltaglue), where initiation occurs at the cathode terminal. Structure–activity relationships of Voltaglue as a function of AC frequency at currents of 1–3 mA are evaluated against direct currents, migration rate, storage modulus, and lap-shear adhesion on ex vivo tissue mimics. Numerous improvements in electrocuring are observed with AC stimulation vs direct current, including a 35% decrease in maximum voltage, 180% improvement in kinetic rates, and 100% increase in lap-shear adhesion at 2 mA. Li+ ion electrolytes and curing at 4 °C shifts curing kinetics by +104% and −22% respectively, with respect to the control ion (Na+ ion at 24 °C), suggesting that electrolyte migration is the rate-limiting step. Li+ ion electrolytes and curing at 50 °C improve storage modulus by 110% and 470%, respectively. Further evaluations of electrocured matrices with 19F NMR, solid-state NMR, and infrared spectroscopy provide insights into the probable cross-linking mechanisms.